Correlation Between Post Natal Care and Premature Baby Health in the RSKD Ibu & Anak Siti Fatimah Makassar - Ratna; Jamila Kasim; Sri Suryani; Oktovina Suka (International Journal of Clinical Inventions and Medical Sciences, 2020)
Premature babies are babies born alive before the 37th week of gestational age which is calculated from the first day of the last menstruation. Baby care in an incubator is a method of caring for infants by putting the baby in a device that serves to help create adequate ambient temperatures with normal temperatures. Providing optimal nutrition is important in the management of premature and very low weight babies. Prevention of infection is the most important part of every newborn component. The purpose of this study was to determine the relationship between post natal care and premature baby health at the Siti Fatimah Makassar Hospital. This study is a cross sectional study, the population in this study were all babies born at gestational age less than 37 weeks and who were temporarily undergoing treatment at Siti Fatimah Hospital Makassar. Sampling using purposive sampling, obtained 30 samples according to inclusion criteria. Data collection is done in a primary way with direct observation techniques. The collected data is then processed and analyzed using Microsoft Excel computer programs and statistical programs (SPSS) version 6.0. Data analysis includes univariate analysis by looking for frequency distribution, bivariate analysis with chi-square test (x <0.05), to determine the relationship between variables. The results of the bivariate analysis found a relationship between postnatal care with premature infant health (p = 0.033). So it can be concluded that there is a relationship between post natal care with premature baby health at the Siti Fatimah Makassar Hospital. Therefore, paramedics should make efforts to continuously improve health services and carry out care of premature babies properly and apply optimal care facilities. For further research, researchers can conduct studies on other treatments provided to premature babies.